Darbarahi-yi akharin khiyanati Qasimlu (az muzakirahju'i ta chakarmanishi) : (Anjumani Danishjuyani Musalmani Faransah (Havadarani Sazmani Mujahidini Khalqi Iran))
On Qasimlu's latest betrayal (from negotiation to servitude). Including: Mr Qasimlu's delusional remarks (by Dr Manuchihr Hizarkhani) and a report by Voice of Mujahid (7 July 1988).